E-VILLAGE BUDGETING : EFEKTIVITAS PENCEGAHAN FRAUD PADA PENGELOLAAN KEUANGAN DESA DI KABUPATEN BANYUWANGI - Satia Utama, Anak Agung Gde; Zahari, Afika Rana (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2019)
This study aims to examine whether the current village financial management system in Banyuwangi that uses E-Village Budgeting has been effective in preventing the possibility of fraud in managing village finances. The theories construct these researches are the fraud triangle theory, the fraud management process and ISO 9126. This study used qualitative exploratory methods. This study used the most common data analysis techniques, Max Weber's ideal type. This type is a model or mental abstraction of relationships or social processes. The typical variety is a clear standard where data or